2006
DOI: 10.4049/jimmunol.177.2.991
|View full text |Cite
|
Sign up to set email alerts
|

CD8α Coreceptor to Improve TCR Gene Transfer to Treat Melanoma: Down-Regulation of Tumor-Specific Production of IL-4, IL-5, and IL-10

Abstract: Therapeutic success of TCR gene transfer to treat tumors depends on the ability of redirected T cells to become activated upon tumor recognition in vivo. Help provided by tumor-specific Th1 cells is reported to relieve T cells from an anergized state and to induce tumor regression. We recently demonstrated the ability to generate melanoma-specific Th1 cells by genetic introduction of both a CD8-dependent TCR and the CD8α coreceptor into CD4+ T cells. In this study, we analyzed a TCR that binds Ag independently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 50 publications
1
20
1
Order By: Relevance
“…Primary human T lymphocytes of healthy donors, pre-activated with anti-CD3 mAbs were transduced with TCR-positive retroviruses produced by the packaging cell line Phoenix-Amp (32, 33). A retroviral vector encoding human CD8α (34) was used to transduce Jurkat T cells prior to transfer of TCR genes (35). Transduction with Mock genes served as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Primary human T lymphocytes of healthy donors, pre-activated with anti-CD3 mAbs were transduced with TCR-positive retroviruses produced by the packaging cell line Phoenix-Amp (32, 33). A retroviral vector encoding human CD8α (34) was used to transduce Jurkat T cells prior to transfer of TCR genes (35). Transduction with Mock genes served as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Lately, the use of CD4+ T cells transduced to express the α/β chains of a relevant MHC class I-restricted tumor epitope specific TCR has emerged as a mechanism to achieve that goal [4; 5; 6; 7; 8]. That such MHC class-I restricted epitope specific TCR-engineered CD4+ T cells recognize the epitope on MHC class-I molecules with or without the requirement of co-receptor (i.e., CD8 molecules) engagement and exhibit effector function has been described by several groups in animal models [4; 5] as well as in human systems [9; 10; 11; 12]. We have shown that human CD4+CD25− T cells transduced to express the α/β TCR chains specific for the Melan-A/ MART-1 27–35 epitope, express type I cytokines and exhibit cytolytic function in a co-receptor-independent fashion [12].…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic benefit of antigen-specific IFN γ production have initiated studies in which CD4 T cells were used as recipient T cells for MHC class I-restricted TCR. Not only can CD4 T cells be functionally endowed with MHC I-restricted TCR via gene transfer [19, 67, 68], but also can genetic cointroduction of CD8 α skew TCR-engineered T cells towards an antigen-specific Th1 type T-cell response [69]. Vice versa, the introduction of a MHC class II TCR and CD4 coreceptor in CD8 T cells may lead to the generation of T cells with combined helper and effector T-cell functions [66].…”
Section: Discussionmentioning
confidence: 99%